Efectos de la balanza comercial no petrolera en el crecimiento económico ecuatoriano, período 1996-2021. - Buele Illescas, Kerly Marilin; Saenz Lluipuma, Jhon Andres (My University, 2022)
In Ecuador, the non-oil trade balance is an important variable because it records the purchase (imports) and sale (exports) of raw materials such as bananas, coffee, shrimp and roses, which allows determining the prosperity, recession or economic decline of the non-oil sector. Due to this importance, the present research is developed with the objective of "analyzing the effect of the non-oil trade balance in the Ecuadorian economic growth during the period 1996 - 2021" for the analysis we used data from official sources (BCE and World Bank), with which a "log-log" model was elaborated, on the other hand, using the function of the "log-log" model. On the other hand, using the Cobb Douglas production function, it was determined whether the Non-oil Trade Balance generates increasing or decreasing returns to scale.
En Ecuador la Balanza Comercial No Petrolera resulta ser una variable importante pues en ella se registra la compra (importaciones) y venta (Exportaciones) de materias primas como el banano, el café, el camarón y las rosas, lo cual permite determinar la prosperidad, recesión o declive económico del sector no petrolero. A raíz de esta importancia, la presente investigación se desarrolla con el objetivo de “analizar el efecto de la balanza comercial no petrolera en el crecimiento económico ecuatoriano durante el periodo 1996 - 2021” para el análisis se utilizó datos de fuentes oficiales (BCE y Banco Mundial), con lo que se elaboró un modelo “log-log” , por otra parte utilizando la función de producción de Cobb Douglas se determinó si la Balanza Comercial No Petrolera genera rendimientos a escala crecientes o decrecientes.
Keywords: BALANZA COMERCIAL NO PETROLERA; EXPORTACIONES; IMPORTACIONES; CRECIMIENTO ECONÓMIC